Ethnographic and Phenomenological Research in the Business Field: Theoretical and Applied Analysis - Alshahrani, Abdullah (The Arab Journal of Administration, 2023)
In order to determine how business studies can be used and adapted to phenomenological and ethnographic methods in the context of the business field; The researcher providing in this paper a theoretical explanation and applied aspect of the two methods of qualitative research by reviewing a group of empirical studies in a number of scientific papers in the business field published between 2020 and 2022 in the SAGE journal digital library, including: Three studies that used Phenomenology method, and five with ethnographic approach. Regarding to the theoretical aspect, the study shows that phenomenology studies the different experiences it encounters from a subjective or first-person point of view (the subjective point of view). In ethnographic approach is concerned with revealing the mutual form of social interactions in certain contexts that create order, this is done by observing, observing, and interpreting the procedures and practices that members of society perform in their daily lives (the point of view of the respondent about the community or the subject). Therefore, the ethnographic approach is a way to frame observations and inquiries in social interactions in a way that confirms how individuals understand their own worlds in which they live, and it does not concern about individuals like phenomenology, but it is concerned with the so-called participating competencies as group members. In practical terms, the article provided information on the selected research, including research objectives, reasons for selecting the method, sample size, target population, research duration, and applied procedures for data collection and data analysis. The results of this work can contribute to understanding how to apply phenomenological and ethnographic methods in business research.